(untitled) (American Journal of Islam and Society, 1989)
Abstract In this paper I have tried to argue that the two widely used paradigms of Individualism in Western social science, and Collectivism in Soviet social science, are not appropriate for Islamic social science on account of the secularism (disregard of revelation) of the former and the "scientific atheism" of the latter. I have funher tried to argue that the hypothetico-deductive and empirical methodology (often called logical positivism) of natural and physical science is not appropriate for social and behavioral science in general, and Islamic social behavioral science in particular. It would be more fitting to regard the various disciplines of social and behavioral science as moral sciences in order to incorporate the values, morals, and purposes of society in theorybuilding and hypothesis-formation. Accordingly, I am arguing in favor of a moral explanation of human behavior and social processes. A moral explanation is one which seeks to discover the causes (immediate antecedents) as well as reasons (including motives and intentions) behind human behavior with the greater responsibility for the explanation resting with the latter. A paradigm, conceptual framework, or what is called grand theory is essential for the formulation of theories in various fields of social and behavioral sciences, on the one hand, and for guiding empirical research. on the other. Western social science and Soviet social science have their respective paradigms. The immediate need of Islamic social science is to construct a distinguishable paradigm of its own. I have tried to formulate a list of the underlying concepts of such a possible paradigm, conceptual framework, or grand theory, but not such a theory per se. Finally, I have made the suggestion that, inasmuch as the understanding of human behavior is our goal, the social and behavioral scientist could enhance the understanding of human and social phenomena by trying to understand his/her own motives, behavior, and actions ...